Language Features of Autistic Character in Please Stand By Film: Psycholinguistic Analysis - Rohani, Siti; Valiantien, Nita Maya; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Persons with autism disorder generally have difficulty in social and communication. Due to these impairments, they are often ignored and misunderstood by others. One of the phenomena of autism is portrayed in a film entitled Please Stand By. This study is aimed to analyze the features of autistic person and the kinds of responses given by autistic person represented by Wendy, an autistic character in the film. This study employed descriptive qualitative method and a psycholinguistic approach. In addition, this study used Wing and Gould’s theory to identify the features of autistic person and Rothwell’s theory to identify the kinds of responses given by autistic person. The results of this study show two important points. First, based on the findings of this study, there are three features of autistic person experienced by Wendy, they are qualitative impairment in reciprocal social interaction, qualitative impairment in verbal and non-verbal communication and in imaginative activity, and markedly restricted repertoire of activities and interests. Second, there are three kinds of responses given by Wendy, they are cognitively irrelevant responses, cognitively relevant responses, and cognitively disruptive and socially inappropriate responses. In cognitively disruptive and socially inappropriate responses, there are odd responses, relevant but not too polite responses, and marginally relevant responses. The findings reveal that persons with autism can provide relevant responses to others even though they have difficulty in social and communication.